Relationship between Personality and Job Engagement: A Study of Nursing Employees of Leading Private Healthcare Organizations in Colombo District, Sri Lanka - Dilmini, H.M.D; Thalgaspitiya, U.K (University of Sri Jayawardenepura, 2020)
Job engagement is considered as a significant topic in organizational research due to its many effects on the overall well- being of the organization. One of the most important management-focused concepts is Employee Engagement which helps to compete and perform in a turbulent and competitive environment in order to achieve organizational goals and objectives. Personality is one of the antecedents to job engagement. In this study, an attempt was made to identify the relationship between personality and job engagement in leading private healthcare organizations in Colombo district, Sri Lanka. A structured questionnaire with two instruments, including 47 questions was used to test the hypotheses. This research work was carried out covering a sample of 260 out of 800 nursing staff attached to the leading private healthcare organizations in Colombo district, Sri Lanka. Responses from the survey were statistically analyzed with Pearson’s correlation coefficient and multiple regressions using 23.0 version of SPSS software. The results of the study expressed that there is a positive moderate relationship between personality factors (neuroticism, extraversion, openness to experience, agreeableness and conscientiousness) and job engagement of employees. However, Neuroticism also positively correlates with job engagement by opposing previous research findings. On the other hand, conscientiousness is considered as the most determinant personality trait on job engagement. This study will help to get a better understanding of nursing employee’s personality and its relationship to their job engagement. This understanding can also better inform administrators to comprehend the importance of dispositional factor in determining job engagement.